The labour market effects of international trade in the presence of vertical product differentiation: Some methodological remarks in retrospect - Giuseppe Celi (Journal of Risk and Financial Management, 2021)
The paper retrospectively analyses the issue of the impact of international trade on developed countries' labour markets in the 1990s, when the majority of academic opinion denied the role of trade in the misfortunes of unskilled workers. An analytical framework is proposed in which intra-industry trade is explained in terms of countries' factor endowments and factor intensities of goods. Unlike the traditional Heckscher-Ohlin model of inter-industry trade, the model suggested here is more consistent with stylised facts about North-South trade. The paper also proposes a method for empirically assessing factor substitution effects at the product level. Inferring the factor content of intra-industry trade from the inter-sectoral relationship between factor intensity and average unit values of exports, the paper found that the labour market effects of intra-industry trade add significantly to the estimated factor market impact of trade.
Keywords: F1; 330; intra-industry trade; labour market effects of international trade; North-South trade; quality differentiation